1999
DOI: 10.1002/jlb.66.6.889
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage responses to hypoxia: relevance to disease mechanisms

Abstract: Macrophages are ubiquitous in the stromal compartment of tissues under normal physiological conditions and the number of these cells increases markedly with the onset and progression of many pathological states. The mechanisms underlying this response are well described in such conditions as wound healing and malignant tumors, where tissue-specific signals enhance the extravasation of blood monocytes and their subsequent differentiation into macrophages. Recent evidence suggests that macrophages may also be st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
302
1
31

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 365 publications
(343 citation statements)
references
References 86 publications
9
302
1
31
Order By: Relevance
“…Responses to many osteolytic agents, including acidosis, are similarly prostaglandin-dependent in calvarial cultures . Prostaglandins also stimulate osteoclast formation (Collins and Chambers, 1992;Lader and Flanagan, 1998), and commonly mediate hypoxic responses in other cell types, such as macrophages (Lewis et al, 1999). Secondly, hypoxia stimulates purine nucleotide release from endothelial cells (Bodin and Burnstock, 1995), and we have previously shown that ATP and ADP are powerful osteolytic agents, acting through P2 receptors on bone cells (Morrison et al, 1998;Hoebertz et al, 2000Hoebertz et al, , 2001; this mechanism could account for some of the resorptive action of hypoxia in intact bone but it remains to be investigated whether nucleotide release from other cell types in bone might also be enhanced by low PO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Responses to many osteolytic agents, including acidosis, are similarly prostaglandin-dependent in calvarial cultures . Prostaglandins also stimulate osteoclast formation (Collins and Chambers, 1992;Lader and Flanagan, 1998), and commonly mediate hypoxic responses in other cell types, such as macrophages (Lewis et al, 1999). Secondly, hypoxia stimulates purine nucleotide release from endothelial cells (Bodin and Burnstock, 1995), and we have previously shown that ATP and ADP are powerful osteolytic agents, acting through P2 receptors on bone cells (Morrison et al, 1998;Hoebertz et al, 2000Hoebertz et al, , 2001; this mechanism could account for some of the resorptive action of hypoxia in intact bone but it remains to be investigated whether nucleotide release from other cell types in bone might also be enhanced by low PO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, hypoxia stimulates purine nucleotide release from endothelial cells (Bodin and Burnstock, 1995), and we have previously shown that ATP and ADP are powerful osteolytic agents, acting through P2 receptors on bone cells (Morrison et al, 1998;Hoebertz et al, 2000Hoebertz et al, , 2001; this mechanism could account for some of the resorptive action of hypoxia in intact bone but it remains to be investigated whether nucleotide release from other cell types in bone might also be enhanced by low PO 2 . Thirdly, one of the major effects of hypoxia on cells is to stimulate the production of potent angiogenic factors such as VEGF, tumor necrosis factor-a, and fibroblast growth factors (Lewis et al, 1999); these factors are also stimulators of the formation and/or function of osteoclasts (Simmons and Raisz, 1991;Nakagawa et al, 1999Nakagawa et al, , 2000Suda et al, 2001). It is already well documented that hypoxia increases VEGF production by osteoblasts (Steinbrech et al, 1999(Steinbrech et al, , 2000aAkeno et al, 2001), and VEGF production by human peripheral blood-derived macrophages is also strongly upregulated by hypoxia (Lewis et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A common denominator of many pathological lesions is hypoxia, a condition of low oxygen tension that occurs, for example, within the tumor mass or in inflammatory areas. Mf respond to hypoxia 9,10 and can be engineered to express therapeutic genes under these conditions 11,12 using synthetic promoters containing the hypoxia-responsive element (HRE), which is specifically transactivated under hypoxic conditions (reviewed in Lewis et al 10 and Semenza 13 ).…”
Section: Introductionmentioning
confidence: 99%